GEJOLAK BATIN TOKOH UTAMA DALAM NOVEL 00.00 SEPASANG LUKA YANG BERAKHIR DUKA KARYA AMEYLIA FALENSIA (KAJIAN PSIKOLOGI SASTRA) - Feni Ansari; Aslan Aslan; Elsa Mulya Karlina (CV. ADIBA AISHA AMIRA, 2025)
This study aims to understand the inner turmoil of the main character in the novel 00.00 A Pair of Wounds Ending in Sorrow by Ameylia Falensia. This novel provides inspiration, motivation, and a moral message for its readers. Data is presented in the form of quotations regarding the forms of inner turmoil, the factors causing it, and the impacts of it. This type of research is library research (literature review) using a qualitative approach. The research data sources include the main source, namely the novel 00.00 A Pair of Wounds that End in Sorrow by Ameylia Falensia, and supporting data, namely documentary data that is relevant to the research focus such as scientific journals, theses and other documents. The data analysis technique used in this research is library data collection, reading and recording and processing library collection materials without requiring field research. The results of the study concluded that: (1) Forms of inner turmoil can be described through basic emotions in the novel 00.00 A Pair of Wounds that End in Sorrow by Ameylia Falensia in the form of: a) happiness, b) anger, c) fear, d) sadness. (2) The factors that cause inner turmoil can be described in the novel 00.00 A Pair of Wounds that End in Sorrow by Ameylia Falensia, that the factors that occur occur between a character and themselves or outside of themselves, namely internal factors in the form of: a) success and failure, b) shame, c) guilt and regret. factors are a) love, and b) hate. (3) The impacts of the inner turmoil experienced by the main character in the novel 00.00 A Pair of Wounds Ending in Sorrow by Ameylia include: a) pain, b) disgust, c) pleasure.